Examining suicidality and associated risk factors among refugee children and adolescents in Uganda - Ainamani, Herbert E.; Mbwayo, Anne Wanjiru; Mathai, Muthoni; Karlsson, Linnea; Rukundo, Godfrey Zari; Hall, Jonathan (BioMed Central, 2026)
Background
Suicide is a leading cause of death among young people globally. Although suicidality has been studied in various populations, limited research has focused on refugee youth in low and middle-income countries. This study aimed to assess the prevalence of suicidal ideation, suicide attempts, and methods of attempted suicide among refugee children and adolescents in southwestern Uganda. We also examined risk factors associated with suicidal ideation in this population.
Methods
We conducted a cross-sectional study of 325 refugee children and adolescents selected through simple random sampling in Nakivale Refugee Settlement, southwestern Uganda. Suicidal behavior and post-traumatic stress disorder (PTSD) were assessed using the Mini International Neuropsychiatric Interview for Children and Adolescents, version 7.02 (MINI-KID). Additional variables—including war-related trauma and post-migration experiences were measured using structured checklists administered through KoboCollect. The data were then exported to STATA 17 for analysis. Descriptive statistics were used to calculate the prevalence of suicidal ideation, attempts, and means, while bivariate and multivariate logistic regression analyses were conducted to identify factors associated with suicidal ideation.
Results
Of 325 participants, 129 (40%) reported suicidal ideation, and among these, 70 (54%) had formulated a suicide plan. Of those with a plan, 13 (19%; (4.3% of the total sample)) had attempted suicide. The most common method of attempted suicide was self-poisoning (4/13, 31%), followed by hanging or drowning (3/13, 23%), self-stabbing (2/13, 15%), and self-imposed accidents (1/13, 8%). In multivariate analyses, suicidal ideation was significantly associated with exposure to war-related trauma (OR = 2.30, 95% CI: 1.35–3.94, p = 0.002), PTSD (OR = 5.47, 95% CI: 2.15–13.94, p < 0.001), and being an unaccompanied minor (OR = 6.14, 95% CI: 2.13–17.68, p = 0.001).
Conclusion
Suicidal ideation is highly prevalent among refugee children and adolescents in Nakivale Refugee Settlement. Prevention efforts should prioritize trauma-related factors, PTSD, and the specific needs of unaccompanied minors.